A bibliometric analysis of 3D printing for bone tissue regeneration - Idris, Maizlinda Izwana; Hussin, Mohamed Saiful Firdaus; Abdullah, Hasan Zuhudi; Roslan, Mohammad Fikrey; Muhamad Damanhuri, Amir Abdullah; Mukhtar, Mohd Fariduddin (Universiti Putra Malaysia, 2025)
3D printing technology in tissue regeneration discipline played a pivot role in the sustainable growth of human healthcare. Publication based on 3D printing and tissue regeneration discipline has exhibited an exponential growth due to the vast expansion of the research output. In regard to current publications, the authors investigated the trends regarding 3D printing technology in tissue regeneration discipline, focusing on bone. An analysis using the keywords “3D printing” and “bone tissue regeneration” revealed that 261papers were published between 2015 and 2024. The number of publications on these topics increased significantly, raising from 2 in 2015 to 70 in 2024. The materials extrusion, directed energy deposition, powder bed fusion, materials jetting, and photopolymerization were currently the most often types of technology used to produce 3D biomedical products related to bone tissue regeneration. Meanwhile, metal, polymer, ceramic, composite, smart material, and special material were the most frequently used materials as matrix or filler in biomedical 3D printing technology. Studies in the current literature reveal that composites are favored due to material properties that can be customized to meet specific requirements including mechanical strength, heat resistance, flexibility, and chemical resistance. The Chinese government has strategically invested in regenerative medicine and 3D bioprinting to address healthcare challenges and position the nation at the forefront of medical innovation. As for method, fused deposition modeling (FDM) is frequently chosen among researchers due to cost-effectiveness, user-friendly and compatibility to wide range of thermoplastic materials. This review will provide significant support by offering scientific insights to assist future research in the field of tissue regeneration.